A high efficiency zero-emission argon split cycle engine. (May 2022) - Dong, Guangyu; Du, Qiang; Li, Liguang; Atkins, Andy; Morgan, Robert
The argon Otto cycle engine concept is a new approach to achieve both high efficiency and zero emissions. The high specific heat ratio (γ) of argon delivers an efficiency uplift relative to conventional air breathing engines. However, the high γ also results in high end of compression temperature and high risk of pre-ignition (knock). This limits the compression ratio (CR) and hence thermal efficiency (η) of an argon engine. The split cycle is a novel internal combustion engine thermodynamic cycle which yields high thermal efficiency under low CR conditions. In this paper, we propose a new engine concept combining the merits of both argon engine and split cycle engine. A theoretical analysis was conducted to investigate the fundamental operating mechanisms of the argon split cycle engine (ASCE). Experiments were undertaken to measure combustion parameters such as heat release with an argon-oxygen-hydrogen mixtures. A one-dimensional engine model was constructed and validated using the test results. Optimisation of the ASCE using the 1D validated simulation showed that a maximum 75% of the exhaust energy can be recovered in the ASCE. Compared to an engine with a conventional Otto cycle, the ideal thermal efficiency of ASCE with a CR = 6 is equal to an Otto cycle argon engine with a CR = 27. Consequently, an indicated thermal efficiency of 66% can be expected in a practical ASCE with low compression ratio (CR = 6).